2016
DOI: 10.33834/bkr.v2i1.49
|View full text |Cite
|
Sign up to set email alerts
|

Growth Regimes in a Structural Economic Dynamic Approach to the Neo-Kaleckian Model

Abstract: Following the insight that profits influence investment, providing not only the motive for it but also the means,we consider the natural rate of profit as one of the determinants of investment in a disaggregated version of the Neo-Kaleckian model of economic growth.By adopting this approach, it is shown that the structural economic dynamic is conditioned not only to the patterns of evolving demand and diffusion of technological progress but also to the distributive features of the economy, which can give rise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Here it is worth noting the difference between the Kaleckian approach and the Kaldorian approach, given that they both considered to be fundamental lines of thought in the theory of income distribution For instance, unlike the Kaldor-Robinson model, Kaleckian models assume that some sort of monopolistic or oligopolistic competition dominates the markets in which price responds inflexibly to the change in demand and supply Another difference is related to the rate of capacity utilization In the Kaleckian models, the rate of capacity utilization is not considered to be exogenously fixed at some normal rate, in this sense, it becomes endogenous in the Kaleckian approach (Hein, 2014) The main premise of Kaleckian models, which is wage-led growth, was interpreted by the basic model of Kalecki-Steindl under strong assumptions including: no saving out of wages, no foreign trade and strong accelerator effect in the investment function They claimed that growth can be wage-led due to a combination of two effects, the increase in the aggregate demand resulting from the increase in workers' consumption due to the impact of higher real wages, on one hand, and a strong accelerator effect of the resulting rise in capacity utilization, which enhances realized investment, on the other hand That is increasing the profit rate, despite the decrease in the profits share (Blecker and Setterfield, 2019) Later, Kaleckian models became subject to a number of modifications, the most important of which were presented by Rowthorn (1981) and Dutt (1984Dutt ( , 1987, who formed the so-called neo-Kaleckian, or the second generation of Kalecikan model They independently developed models that treat the capacity utilization and growth rate as an endogenous variable In these models they consider the investment to be an increasing function of both the profit rate and capacity utilization, unlike the Kaldor-Robinson model wherein only the rate of profit determines the rate of investment growth (Araujo and Teixeira, 2016) Thus, in this sense, while the neo-Kaleckian models assumes that the capacity utilization is endogenous and the profit share is exogenous, the growth effects of aggregate-demand work via capacity utilization In contrast, the models in the Cambridge growth theory are based on opposite assumptions where the profit share is endogenous and capacity utilization is exogenous, making these models work via the profit share (Palley, 2017) One of the most important finding of neo-Kaleckian models relates to the possibility of a stagnationist regime, in which the increase in the profit share necessar-ily implies a reduction in capacity utilization and economic growth This finding, as Palley (2014) pointed out, is clearly demonstrated in the model developed by Dutt (1984) where he indicates that if the Keynesian expenditure multiplier stability condition holds, the economy can only be wage-led or conflictive However, this result has been challenged by Amit Bhaduri and Steven Marglin in the early 1990s, after making adjustments to the neo-Kaleckian models They concluded that the stagnation is no longer one of its necessary outcomes Furthermore, they also identified a completely opposite situation in which the demand for investment responds positively to the increase in the profits share and called this case "exhilarationism" They also argue that the "exhilarationism" case can be seen in the context of international price competition The increase in external competi...…”
Section: The Evolution Stagesmentioning
confidence: 99%
“…Here it is worth noting the difference between the Kaleckian approach and the Kaldorian approach, given that they both considered to be fundamental lines of thought in the theory of income distribution For instance, unlike the Kaldor-Robinson model, Kaleckian models assume that some sort of monopolistic or oligopolistic competition dominates the markets in which price responds inflexibly to the change in demand and supply Another difference is related to the rate of capacity utilization In the Kaleckian models, the rate of capacity utilization is not considered to be exogenously fixed at some normal rate, in this sense, it becomes endogenous in the Kaleckian approach (Hein, 2014) The main premise of Kaleckian models, which is wage-led growth, was interpreted by the basic model of Kalecki-Steindl under strong assumptions including: no saving out of wages, no foreign trade and strong accelerator effect in the investment function They claimed that growth can be wage-led due to a combination of two effects, the increase in the aggregate demand resulting from the increase in workers' consumption due to the impact of higher real wages, on one hand, and a strong accelerator effect of the resulting rise in capacity utilization, which enhances realized investment, on the other hand That is increasing the profit rate, despite the decrease in the profits share (Blecker and Setterfield, 2019) Later, Kaleckian models became subject to a number of modifications, the most important of which were presented by Rowthorn (1981) and Dutt (1984Dutt ( , 1987, who formed the so-called neo-Kaleckian, or the second generation of Kalecikan model They independently developed models that treat the capacity utilization and growth rate as an endogenous variable In these models they consider the investment to be an increasing function of both the profit rate and capacity utilization, unlike the Kaldor-Robinson model wherein only the rate of profit determines the rate of investment growth (Araujo and Teixeira, 2016) Thus, in this sense, while the neo-Kaleckian models assumes that the capacity utilization is endogenous and the profit share is exogenous, the growth effects of aggregate-demand work via capacity utilization In contrast, the models in the Cambridge growth theory are based on opposite assumptions where the profit share is endogenous and capacity utilization is exogenous, making these models work via the profit share (Palley, 2017) One of the most important finding of neo-Kaleckian models relates to the possibility of a stagnationist regime, in which the increase in the profit share necessar-ily implies a reduction in capacity utilization and economic growth This finding, as Palley (2014) pointed out, is clearly demonstrated in the model developed by Dutt (1984) where he indicates that if the Keynesian expenditure multiplier stability condition holds, the economy can only be wage-led or conflictive However, this result has been challenged by Amit Bhaduri and Steven Marglin in the early 1990s, after making adjustments to the neo-Kaleckian models They concluded that the stagnation is no longer one of its necessary outcomes Furthermore, they also identified a completely opposite situation in which the demand for investment responds positively to the increase in the profits share and called this case "exhilarationism" They also argue that the "exhilarationism" case can be seen in the context of international price competition The increase in external competi...…”
Section: The Evolution Stagesmentioning
confidence: 99%